2021
DOI: 10.1002/hbm.25450
|View full text |Cite
|
Sign up to set email alerts
|

Both frontal and temporal cortex exhibit phonological and semantic specialization during spoken language processing in 7‐ to 8‐year‐old children

Abstract: A previous functional magnetic resonance imaging (fMRI) study by Weiss et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 46 publications
6
28
3
Order By: Relevance
“…Left STG plays an essential role in word segmentation or analyzing words' phonological and morphological constituents (Arredondo et al, 2015;Friederici & Gierhan, 2013;Friederici et al, 2003;Leminen et al, 2019;Leonard & Chang, 2014;Liebenthal et al, 2005;Wang et al, 2021). For instance, Arredondo et al (2015) showed that children with stronger morphological awareness skills exhibited stronger left STG activation during a morphology task.…”
Section: Home Language Proficiency Effects In Bilingual's Englishmentioning
confidence: 99%
“…Left STG plays an essential role in word segmentation or analyzing words' phonological and morphological constituents (Arredondo et al, 2015;Friederici & Gierhan, 2013;Friederici et al, 2003;Leminen et al, 2019;Leonard & Chang, 2014;Liebenthal et al, 2005;Wang et al, 2021). For instance, Arredondo et al (2015) showed that children with stronger morphological awareness skills exhibited stronger left STG activation during a morphology task.…”
Section: Home Language Proficiency Effects In Bilingual's Englishmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 12, 2022. ; https://doi.org/10.1101/2022.08.11.503597 doi: bioRxiv preprint 4 4 regions emerge in early childhood (ages 5-6) (Weiss et al, 2018), the frontal regions are slower to develop their specificity to linguistic content, emerging only after 7-8 years of age (Wang et al, 2021). Others have seen frontal language network activation in children as young as 4 years old (Olulade et al,.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work suggests a functional separation of the dorsal versus ventral left IFG for phonological and semantic processing (e.g., Coltheart et al, 2005;Hodgson et al 20221;Jobard et al, 2003;Mathur et al, 2020;Vigneau et al, 2011;Wang, Yamasaki, Weiss, & Booth, 2021). Phonological processing of speech sounds involves perceptual processing in the STG and articulatory processing in the dorsal IFG (Hickok & Poeppel, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…Phonological specialization in the left STG is evident in children by age five (e.g., Mathur et al, 2020;Weiss, Cweigenberg, & Booth, 2018;Yamasaki et al, 2021), whereas specialization in the dorsal IFG is thought to develop later around age seven (e.g., Wang, Yamasaki, Weiss, & Booth, 2021;Yamasaki et al, 2021). Notably, the engagement of this dorsal fronto-temporal pathway during phonological processing is predictive of children's word reading skills throughout reading development (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation